The relationship between stress levels, training intensity, micronutrient intake, and primary dysmenorrhea in athletes - Keysa Sabrina Aisyah; Isti Kumalasari; Muchamad Rizki Sentani; Syifa F. Syihab (Jorpres (Jurnal Olahraga Prestasi), 2026)
Primary dysmenorrhea is commonly experienced by adolescent and adult women, including female athletes. The pain is associated with various factors, such as sociodemographic, psychosocial, lifestyle or health-related factors, and reproductive factors. This study aims to analyze the relationship between stress levels, training intensity, and micronutrient intake with primary dysmenorrhea among female student athletes at SMAN X Bandung and to analyze the most dominant variable associated with primary dysmenorrhea. This research method used a cross-sectional design. The sample consisted of 63 female student athletes at SMAN X Bandung, selected through proportionate stratified random sampling. The Spearman rho correlation test showed that training intensity (p = 0,000; r = 0,507), iron intake (p = 0,000; r = -0,620), vitamin B6 intake (p = 0,000; r = -0,503), and magnesium intake (p = 0,000; r = -0,430) were associated with primary dysmenorrhea in female student athletes. In contrast, stress level and calcium intake (p = > 0,05) were not associated with primary dysmenorrhea in female student athletes. High training intensity was found to increase the risk of primary dysmenorrhea by 13,091 times compared to low training intensity, while iron intake was found to be a protective factor (OR < 1). Monitoring and providing education on stress management, proper training programs, and adequate micronutrient intake are necessary to improve athletes' health and performance. Keywords: Micronutrient Intake; Stress Levels; Training Intensity; Primary Dysmenorrhea